Engineered Silver Nanoparticles, A New Nanoweapon Against Cancer - Ebrahimzadeh, Mohammad A.; Tafazoli, Alireza; Akhtari, Javad; Biparva, Pourya; Eslami, Shahram (Anti-Cancer Agents in Medicinal Chemistry, 2018)
New modifications in nanoparticles changed their applications obviously. Green synthesis of nanoparticles and their biomedical utilizations have been the focus of increasing attention in recent years. Silver nanoparticles (AgNPs) demonstrated surprising effects and many advantageous features for cancer therapy. Investigations indicated the anticancer activity of AgNPs in different ways, comprising cell cycle arrest, DNA damaging and apoptosis, alteration of P53 function, up/down regulation of some important cytokine genes and so on. But some key inquiries like the ability to control the accidental effects of AgNPs, or encompassing process for parcels, which reduces the toxicological profile of nanoparticles, still remained. “Green synthesis” of nanoparticles has been shown to be a kind of approach to resolve the toxicity amounts in a range of 10-18 times. Using distinctive properties of this approach, i.e. as green synthesized silver nanoparticles (G-AgNPs), in order to raise potential therapeutic efficacy, even up to two-fold higher than cis-platin, is going to play a crucial role in cancer treatment and could be considered as a new insight in this field. The current review focuses on the antioxidant activity of G-AgNPs and potential impacts on cancer cells.
Keywords: p53